Prenatal Diagnosis of Pulmonary Atresia With Ventricular Septal Defect and an Aberrant Ductus Arteriosus in a Dextrocardia by Two- and Three-Dimensional Echocardiography: A Case Report - Liang, Lulu; Wang, Yu; Zhang, Ying (Frontiers in Medicine, 2022)
Introduction Prenatal diagnosis of pulmonary atresia is difficult in relative, especially when the pulmonary artery is slim and hypoplastic in development. It is of great importance to search for the blood supply to the pulmonary artery in those fetuses while it challenges most screening sonographers, even fetal echocardiography specialists. We herein report a rare case of pulmonary atresia with ventricular septal defect, complicated with an aberrant ductus arteriosus which provides the blood supply to the pulmonary artery. Besides, the case was also accompanied by cardiac malposition, dextrocardia with situs solitus. The echocardiographic characteristics and autopsy findings are also presented to approach the skill of fetal diagnosis. Case presentation A 30-year-old primigravida woman was referred to our center at gestational age of (24 ± 3) weeks for further fetal cardiac examination for suspected fetal cardiac anomalies. Fetal echocardiography revealed dextrocardia, situs solitus of the atria, an L-ventricular loop, a ventricular septal defect, an enlarged coronary sinus, and pulmonary atresia by transverse scanning. The ductus arteriosus was not present at the three-vessel trachea view with the retrograde flow showing in the pulmonary artery trunk, which suggested the possibility of an aberrant ductus arteriosus. Sagittal and coronal scanning was attempted to find that the pulmonary artery connected with the innominate artery via the aberrant ductus arteriosus. Three-dimensional echocardiography with spatio-temporal image correlation and high-definition flow imaging technique was performed to obtain the three-dimensional rendered image, which clearly showed the malformation in space. The pregnancy was terminated and the gross findings confirmed the prenatal diagnosis. Conclusion A detailed evaluation of fetal cardiac anatomy and hemodynamics is crucial for the detection of an aberrant ductus arteriosus, which plays an important role in the diagnosis of pulmonary atresia with ventricular septal defect. Sagittal and coronal scanning is useful to find the course of this aberrant ductus arteriosus. The three-dimensional echocardiography with spatio-temporal image correlation technique could provide additional spatial information to show great arteries in detail, which can serve as a supplement to traditional two-dimensional modality and benefit examiners to make an accurate diagnosis.